PENGARUH AKTUALISASI DIRI DAN BEBAN KERJA TERHADAP PRESTASI KERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN LABUHANBATU UTARA - Elvina, Elvina (LPPM Universitas Labuhanbatu, 2020)
This study aims to analyze the effect of self-actualization and workload on employee work performance. The population in this study were all employees in the Public Works and Spatial Planning Office of North Labuhanbatu district, totaling 31 people. The analysis used is multiple linear regression analysis using SPSS 20.00 for windows software. The results of this study indicate that self-actualization and workload together have a positive and significant effect on the work performance of employees of the Public Works and Spatial Planning Office of North Labuhanbatu Regency. . This can be seen from the R Square value of 0.687 or 68.7%, the remaining 31.9% can be explained by other variables not included in this research model.